Kajian Intgeral Henstock - Nugraha K. F. Dethan (Program Studi Matematika, Universitas Timor, 2022)
A study of the properties of Henstock integral has been carried out. Henstock integral is an extension of Riemann integral. This is because the Henstock integral is built on the concept of Riemann integral, using the Riemann sum over the partition on the domain interval of a function. The difference lies in controlling the partition. On Riemann integral the control of a partition is roled by a constant positive number, whereas on Henstock integral the control of a partition is roled by possitive function. In this final project, we will learn how to construct the Henstock integral based on the concept of the Riemann integral, the properties of Henstock integral with its example and its relationship with the Riemann integral. The result of the study shows that every function that Riemann integrable is Henstock integrable, but it does not necessarily apply conversely.